Features of Student Youth’s Perception of Russian History: The Influence of Professional Fields and Values - A. A. Andryushkov; A. G. Klius; A. Mihailovski; Yu. N. Sergeev (Высшее образование в России)
This article presents the results of an study conducted in 2023, examining the historical and cultural foundations of Russian identity among modern youth. The study focuses on how affiliation with different social and professional groups shapes their perception of Russian history and culture. Particular emphasis is placed on the processes through which individuals develop a personal understanding of history, offering an innovative approach to analyzing historical memory in relation to Russia’s present and future. The preliminary conclusions drawn from this exploratory research highlight the need for comprehensive models to study the processes of youth identification with Russia.